Advancing large-scale R&D projects towards grand challenges through involvement of organizational knowledge integrators. Issue 1 (2nd January 2019) - Præst Knudsen, Mette; Tranekjer, Tina Lundø; Bulathsinhala, Nadika
Abstract: Public and private funding bodies make massive investments in research to address the grand challenges of the world. These require collective research efforts of a large number of partners to generate knowledge and ultimately create technologies to meet today's grand challenges. Surprisingly, little research is conducted on how to design the research consortia appropriately that actually result in the development of new technologies. This article argues that when organisational knowledge integrators are involved in large-scale projects, they ensure that the research findings of earlier technology development efforts in a project are pulled towards innovation outcomes through their own position in the innovation value chain. This article uses a data-set with 376 collaborative R&D projects within energy technologies. Most importantly, this article confirms the existence of organisational knowledge integrators and the positive effects on project outcomes. These results are discussed with implications drawn for both applicants and funding bodies for future projects.